Análise de deformação da rede GNSS/SP com base na teoria da elasticidade - Caldas, Franciane Lima [UNESP] (2014)
Basing on concepts of elasticity theory, a body under action of external forces or tensions suffers alteration on its original conformation. This change in the body conformation is called deformation. The deformation refers to the several modifications that a body can suffer regarding its shape, dimensions and consequently in its relative position. (LOVE 1994). The purpose of this study was to investigate deformations occurring in the Earth´s surface through the analysis of data from GNSS/SP Network stations. Four IGS stations were used as reference for the calculation of deformations. Any occasional displacements and deformations detected in the Earth’s structure may be the result of bias on analysis and interpretations, once the references point shall be tested whether are stable or not. To asses the displacement and stability of network, were applied the Global Congruency test on the GNSS/SP network stations even as on the stations of reference...